2015
DOI: 10.1007/s13762-015-0856-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of support vector machine and artificial neural network models for soil cation exchange capacity prediction

Abstract: The aim of this study was to compare the performance of support vector machine and artificial neural network techniques to predict the soil cation exchange capacity of an agricultural research station in terms of soil characteristics (clay, silt, sand, gypsum, organic matter). The data consist of 380 soil samples collected from different horizons of 80 soil profiles located in the Khoja (Khajeh) region of Azerbaijani provinces, Iran. The support vector machine and artificial neural network models predict the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 52 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…Other studies use more complex methods such as ANNs, genetic expression programming and support vector networks to estimate CEC from the aforementioned soil properties (e.g. Liao et al ., ; Emamgolizadeh et al ., ; Jafarzadeh et al ., ). Soil specific surface area and the Atterberg limits have also been used to predict CEC (Yukselen‐Aksoy & Kaya, ).…”
Section: Introductionmentioning
confidence: 97%
“…Other studies use more complex methods such as ANNs, genetic expression programming and support vector networks to estimate CEC from the aforementioned soil properties (e.g. Liao et al ., ; Emamgolizadeh et al ., ; Jafarzadeh et al ., ). Soil specific surface area and the Atterberg limits have also been used to predict CEC (Yukselen‐Aksoy & Kaya, ).…”
Section: Introductionmentioning
confidence: 97%
“…(2018) demonstrated that a genetic‐based neural network ensemble (GNNE) is outperformed in estimation of daily soil temperatures as compared to the other methods. Though ANN‐based PTFs performed better in few cases (D'Emilio, Aiello, Consoli, Vanella, & Iovino, 2018; Jafarzadeh, Pal, Servati, FazeliFard, & Ghorbani, 2016), but there are several weaknesses associated with ANN such as several coefficients (not easily interpretable) (Schaap et al., 2001), many types of neurons and their connections (Wösten, Pachepsky, & Rawls, 2001), and over‐fitting and over parameterization due to large number of neurons (Hastie, Tibishrani, & Freidman, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This results is corroborated by Liao et al, (2014), who compared the models performance of multiple stepwise regression, artificial neural network models and SVM for CEC prediction, and attributed their results to a nonlinear relationship between CEC and soil physicochemical properties. In addition, other study (Jafarzadeh et al, 2016) demonstrated that, despite of the ability of SVM to predict CEC in acceptable limits, there is a poor performance in extrapolating the maximum and minimum values of CEC data. Despite this, uncertainties estimated for SVM predictions may not be associated with an incorrect classification.…”
Section: Capacitymentioning
confidence: 98%